Effect of the π-conjugation length on the properties and photovoltaic performance of A–π–D–π–A type oligothiophenes with a 4,8-bis(thienyl)benzo[1,2-b:4,5-b′]dithiophene core - Yin, Ni (Beilstein J Org Chem, 2016)
Benzo[1,2-b:4,5-b′]dithiophene (BDT) is an excellent building block for constructing π-conjugated molecules for the use in organic solar cells. In this paper, four 4,8-bis(5-alkyl-2-thienyl)benzo[1,2-b:4,5-b′]dithiophene (TBDT)-containing A–π–D–π–A-type small molecules (COOP-nHT-TBDT, n = 1, 2, 3, 4), having 2-cyano-3-octyloxy-3-oxo-1-propenyl (COOP) as terminal group and regioregular oligo(3-hexylthiophene) (nHT) as the π-conjugated bridge unit were synthesized. The optical and electrochemical properties of these compounds were systematically investigated. All these four compounds displayed broad absorption bands over 350–600 nm. The optical band gap becomes narrower (from 1.94 to 1.82 eV) and the HOMO energy levels increased (from −5.68 to −5.34 eV) with the increase of the length of the π-conjugated bridge. Organic solar cells using the synthesized compounds as the electron donor and PC(61)BM as the electron acceptor were fabricated and tested. Results showed that compounds with longer oligothiophene π-bridges have better power conversion efficiency and higher device stability. The device based on the quaterthiophene-bridged compound 4 gave a highest power conversion efficiency of 5.62% with a V(OC) of 0.93 V, J(SC) of 9.60 mA·cm(−2), and a FF of 0.63.